2019
DOI: 10.1007/s10734-019-00369-5
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder perception of student employability: does the duration, type and location of work experience matter?

Abstract: Student employability is a key aspect of higher education, with multiple strategies utilised by Higher Education Institutions in an effort to support the employability of their graduates. Despite this little work has been done to examine, and compare, different types of work experience. To advise students appropriately it's important to understand the factors that might influence the perceived value of work experience. The current study investigated three aspects of work experience: type (internship or volunte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 37 publications
1
21
0
3
Order By: Relevance
“…In line with the literature that showed inconsistent evidence about the predictive role of educational level (Judhi et al, 2010;Nauta et al, 2009), educational level was positively associated with employability, although it showed a very low predictive power, compared to the other predictors when dominance analysis was concerned. Finally, no evidence was found in regards to the predictive power of work experience (consistently with the available mixed literature: Irwin et al, 2019;León & Morales, 2019), employability culture (contrary to available evidence : De Vos et al, 2011;Nauta et al, 2009), and family employability support.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In line with the literature that showed inconsistent evidence about the predictive role of educational level (Judhi et al, 2010;Nauta et al, 2009), educational level was positively associated with employability, although it showed a very low predictive power, compared to the other predictors when dominance analysis was concerned. Finally, no evidence was found in regards to the predictive power of work experience (consistently with the available mixed literature: Irwin et al, 2019;León & Morales, 2019), employability culture (contrary to available evidence : De Vos et al, 2011;Nauta et al, 2009), and family employability support.…”
Section: Discussionmentioning
confidence: 52%
“…Judhi et al (2010) focused on the factors that could affect employability, analyzing the association between tenure and external-internal employability and suggesting that a greater work experience increases the individual's chances in the labour market. Also focused on employees, León and Morales (2019) revealed differences in the impact on employability as a function of the tenure characteristics, whilst Irwin et al (2019) showed no impact of the duration of the students' work experience. Whilst the lack of work experience has been traditionally indicated as a challenge when entering employment for young individuals, little is known about the impact of the number of job experiences on job seekers' employment.…”
Section: Antecedents Of Employabilitymentioning
confidence: 94%
“…Further, findings echo previous studies which assert how close alignment between WIL and the students' course content will enhance learning outcomes, enabling them to apply theoretical knowledge (Smith 2012), and providing insight into their career of interest (Jackson 2019). That the length of the activity made no difference to perceived value for enhancing employability aligns with Irwin et al (2019), although Jackson and Wilton (2017) found lengthier internships created more value for career development learning. Pay is unimportant to the value of the activity, contradicting McHugh (2017) who found a positive relationship between compensation and the developmental value of internships.…”
Section: Discussionmentioning
confidence: 86%
“…Employability has contested meaning, often situated in one of three orientations: process and policy; people and capabilities; or employment and performance (Knight & Yorke, 2004;Young, Kelder, & Crawford, 2020). In relation to process, universities are expected to enact responsibility towards students through enabling career development opportunities (Irwin, Nordmann, & Simms, 2019;Jackson & Bridgstock, 2021). Kendal and Waterhouse-Watson (2020), for example, described the role of universities as providing personalised careers advice, including, but not limited to, the pursuit of academic careers.…”
Section: Employabilitymentioning
confidence: 99%